Limitations of Bifurcation Diagrams in Boost Converter Steady-State Response Identification - Stojanović, Željko; Pelin, Denis (International Journal of Electrical and Computer Engineering Systems, 2018)
Steady-state responses of the boost converter operating in discontinuous conduction mode of operation are identified by using bifurcation diagrams as a typical simulation tool for identification of steady-state responses. The structure of simulated bifurcation diagrams is dependent on the initial period of sampling and the initial instant of sampling. The influence of these parameters on calculation of bifurcation diagrams was studied. Some possible issues, pitfalls and misinterpretations are commented as well as some recommendations about steady-state response identification are given.